THE HISTORY AND SPECIFICS OF THE ISLAMIC RENAISSANCE TODAY IN THE CHECHEN REPUBLIC - AKAEV, Vakhit (CENTRAL ASIA AND THE CAUCASUS, 2011)
The specifics of the Islamic renaissance in the Chechen Republic today are related to the increased activity of Muslims and the spread in non-traditional religious trends, as well as to several political and cultural factors that have had an impact on shaping the sociocultural characteristics of Chechen society over the course of history. The extremely complicated religious and political situation in the Chechen Republic today is defined by Islamic traditions, the sociocultural characteristics of the Chechen ethnicity, and the contradictory influence of the new religious trends. It is worth noting that the Islamic trends that became clearly designated right before the collapse of the Soviet Union have added dynamism to the spiritual and religious-political situation not only in the republic itself, but also throughout Russia as a whole. The religious renaissance in Chechnia in the pre-Soviet period was accompanied by an increased interest in Islamic values and the Muslims’ desire to improve the conditions for public worship. In order to satisfy the need for religious knowledge, mosques had to be built, Islamic educational institutions established, and the corresponding literature and periodicals published. On the eve of the Soviet Union’s collapse, the Islamic renaissance in the Chechen-Ingush A.S.S.R. found no obstacles in its path, particularly since the participants in this process were not politically active nor did they call for religious fundamentalism or replacement of the communist slogans with provisions of Shari‘a law. The negative aspects of the Islamic renaissance appeared sometime later when Islamic parties and movements emerged bearing slogans of integrism. They refused to recognize public power and called for creating a theocratic state and full Islamization of secular society. The holders of these ideas, the followers of Wahhabism (Wahhabis), became active after the collapse of the Soviet Union: they began creating organizational structures and press organs, lobbying their interests in the power structures, and gaining access to television. The Wahhabis considered their most important task to be achieving spiritual and political domination in society; these attempts exaggerated the religious contradictions within Muslim society and also gave rise to a conflict between secular and religious values. Such moods were expressed most virulently and manifested in extreme forms in Daghestan, Chechnia, Ingushetia, and KabardinoBalkaria. Many religious-political and sociocultural phenomena relating to the Islamic renaissance can be analyzed using the example of the Chechen Republic based on historical facts.